2016
DOI: 10.1371/journal.pone.0163624
|View full text |Cite
|
Sign up to set email alerts
|

Proficiency in Motivational Interviewing among Nurses in Child Health Services Following Workshop and Supervision with Systematic Feedback

Abstract: BackgroundResearch on training in motivational interviewing (MI) has shown eroding skills after workshops not followed by additional training input (supervision/coaching). There is a need for more research evaluating different types and lengths of post-workshop training with follow-up periods extending six months. This study is an extension of a previous evaluation of the level of proficiency in MI after workshop and four sessions of supervision among nurses in Swedish child health services.AimsTo explore the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…The improvement in MI skills reached by our participants is similar to that reported in other studies on training of professionals in routine work situations 23 32–34. Only 29 per cent of participants reached ‘moderate competency’ and only 6 per cent reached overall ‘fair competency’ according to the classification suggested by Moyers et al 29.…”
Section: Discussionsupporting
confidence: 90%
“…The improvement in MI skills reached by our participants is similar to that reported in other studies on training of professionals in routine work situations 23 32–34. Only 29 per cent of participants reached ‘moderate competency’ and only 6 per cent reached overall ‘fair competency’ according to the classification suggested by Moyers et al 29.…”
Section: Discussionsupporting
confidence: 90%
“…In fact, this notable lack of decline in fidelity across 30 months of follow up is one of the study's most significant strengths. Skill levels following training and consultation have been maintained for 6 to 15 months in studies of clinicians learning Multisystemic Therapy (Henggeler et al, 2008), measurement-based care (Lyon et al, 2017), MI (Persson et al, 2016), and Trauma-Focused Cognitive Behavioral Therapy (Murray, 2017). The current study's two-year sustainment period with its demonstrated lack of deterioration in fidelity is rare in the literature, and supports the effectiveness of ABC consultation procedures.…”
Section: Discussionsupporting
confidence: 63%
“…In total, there were 10 supervisors, which were each responsible for on average five nurses. On average five supervisors participated per workshop ( 20 ).…”
Section: Resultsmentioning
confidence: 99%